DEVELOPMENT OF ANIMATED VIDEOS BASED ON CANVA FOR LEARNING MATHEMATICS TO IMPROVE CLASS STUDENT LEARNING OUTCOMES III AT SD NEGERI 056002 LORONG IBADAH - RISKYKA RISKYKA (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
This research aims to develop canva based animated videos. This research is research and development (RD).This research uses the ADDIE development model. The ADDIE development model consists of analyze, design, develop, implement and evaluate. The research was carried out by SD Negeri 056002 Lorong Ibadah. The research subjects were 25 class III students consisting of 16 male students and 9 female students. The research object is canva based animated video. The collection techniques used are observation, tests and questionnaires. The data analysis techniques used in this research are: (1) feasibility analysis of canva based animated videos); and (2) analysis of the effectiveness of canva based animated videos. Based on the validation results carried out by material experts, 89.75% was in the very feasible category, while the media expert validation results were 93.50% in the very feasible category. Results of trials carried out using canva based animated videos on class III students It is known that as many as 22 students were said to have completed the trial, and 3 students were said to have not completed the trial. This is proven by the percentage result of 92%, which is in the very effective category. Based on the description above, it can be concluded that canva based animated videos are said to be very feasible and very effective for use in the classroom III at SD Negeri 056002 Lorong Ibadah.